Water management options for malaria and climate change mitigation in intensified rice production in Cote d'Ivoire - CGIAR Research Program on Rice (2020)
We are developing a water management approach for reducing the transmission potential of malaria, greenhouse gas emission, water use while increasing rice yield in the research station of Africa Rice Center located at Mbe, Côte d'Ivoire. We found that wet direct sowing increased mosquito density compared to transplanting.